Makna Representasi Ekologis Dalam Kakawin Sangutangis - Savitri, Putu Diah; Suarka, I Nyoman; Erawati, Ni Ketut Ratna (Sphatika: Jurnal Teologi, 2024)
Representation is a way to describe something that someone has seen or experienced. The ecological representation contained in Kakawin Sangutangis includes images of nature which will be depicted through direct depictions of nature itself and wrapped in linguistic style (in kakawin it is called alaṃkara). However, in this research the meaning of ecological representation in Kakawin Sangutangis will be investigated. The aim of this research is to find out the meaning stored behind the ecological representations in KST. So that the general public can understand the meaning of KST. This research is classified as qualitative research with a literary ecology approach assisted by Michael Riffaterre's semiotic theory. Meanwhile, the research methods and techniques that will be used in this research are divided into three parts, namely (1) data collection methods and techniques using library study methods assisted by script transfer, language transfer and note-taking techniques; (2) data analysis methods and techniques that use content analysis methods assisted by analytical descriptive techniques; (3) methods and techniques for presenting data analysis results using formal methods. The results of this research will reveal the meaning stored behind the ecological representations in KST. The meanings found include the meaning of nature conservation and the meaning of self-control. The findings of this research will be useful for motivation in everyday life.